Availability and accessibility of monoclonal antibodies in Bosnia and Herzegovina: Findings and implications - Biljana Tubic (Medicine Access @ Point of Care, 2021)
Background: Monoclonal antibodies (mAbs) represent the most numerous and significant group of biotherapeutics. While mAbs have undoubtedly improved treatment for many chronic diseases, including inflammatory diseases, they are typically expensive for health care systems and patients. Consequently, access to mAbs has been a problem for many patients especially among Central and Eastern European (CEE) countries. However, biosimilars can potentially help with costs, although there are concerns with their effectiveness and safety. This includes biosimilars for long-acting insulin analogues. Aim: Assess the availability and use of biological medicines, including biosimilars within Bosnia and Herzegovina (B&H). Methods: Assess the availability of mAbs via the current lists of approved and accessed mAbs versus those licenced in Europe and the United States and their utilisation, as well as specifically insulin glargine and its biosimilars, within B&H. Results: The availability of the mAbs in B&H appears satisfactory, which is encouraging. However, current usage is limited to a few mAbs which is a concern for subsequent patient care especially with limited use of biosimilars to address issues of affordability. We also see limited use of biosimilar insulin glargine. Conclusion The limited use of mAbs including biosimilars needs to be addressed in B&H to improve the future care of patients within finite resources. We will monitor these developments.